BLOCKCHAIN - HISTORY, FEATURES AND MAIN AREAS OF APPLICATION - Klinger, Bartłomiej; Szczepański, Jacek (Człowiek w cyberprzestrzeni, 2020)
Blockchain technology is viewed as one of the breakthrough information technologies of our time. More than 8 years of history of this technology inextricably links with the history of the digital currency Bitcoin, created by the mysterious Satoshi Nakamoto. Since the first users connected to the Bitcoin network, the perception of blockchain technology has evolved, as a base technology that can be used not only to create other cryptocurrencies than Bitcoin. The emergence of Ethereum, Bitcoin-independent blockchain network, designed by 19-year-old Vitalika Buterina, was also important, for new functional possibilities it offered - smart contracts. The Blockchain, which we know today, very intensely and effectively uses known cryptographic concepts such as one-way hash functions, asymmetrical cryptography or time stamping. With automated consensus mechanisms between blockchain network members, no trusted third party is required to process transactions, whilst intelligent contracts have extended the scope of blockchain technology applications far beyond cryptocurrency transfer. Companies and institutions around the world have discovered the innovative potential of blockchain technology's unique features and are now improving their processes via blockchain technology. The above examples of applications improve the quality of life of ordinary people.